2010
DOI: 10.1186/1471-2105-11-346
|View full text |Cite
|
Sign up to set email alerts
|

Predicting nucleosome positioning using a duration Hidden Markov Model

Abstract: BackgroundThe nucleosome is the fundamental packing unit of DNAs in eukaryotic cells. Its detailed positioning on the genome is closely related to chromosome functions. Increasing evidence has shown that genomic DNA sequence itself is highly predictive of nucleosome positioning genome-wide. Therefore a fast software tool for predicting nucleosome positioning can help understanding how a genome's nucleosome organization may facilitate genome function.ResultsWe present a duration Hidden Markov model for nucleoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(170 citation statements)
references
References 21 publications
8
160
2
Order By: Relevance
“…4). These results were also in agreement with the Nucleosome Positioning Prediction Engine (NuPoP) (51). As predicted by NuPoP, PolyA_1, PolyA_3, and PolyA_4 all had changes in nucleosome positioning compared with the wild-type sequence.…”
Section: Discussionsupporting
confidence: 85%
“…4). These results were also in agreement with the Nucleosome Positioning Prediction Engine (NuPoP) (51). As predicted by NuPoP, PolyA_1, PolyA_3, and PolyA_4 all had changes in nucleosome positioning compared with the wild-type sequence.…”
Section: Discussionsupporting
confidence: 85%
“…3D). Therefore, the phasing pattern of nucleosome occupancy can be roughly predicted using a nucleosome-linker DNA model based on a duration hidden Markov model (dHMM) (45) (Fig. 3D).…”
Section: Significancementioning
confidence: 99%
“…To test this idea, we analyzed these regions with two in silico nucleosome prediction algorithms that predict nucleosome occupancy based on DNA sequence characteristics (61,62) We found that some sites that depend on Mit1 for prevention of nucleosome-free regions appear to be particularly refractory to octamer occupancy and lie near positions predicted to have relatively well-positioned nucleosomes, particularly at REII in the mating-type region and telomere 2R (Fig. 5A and B).…”
Section: ⌬Phd and Mit1mentioning
confidence: 99%
“…The predicted low affinity of these sequences is likely due to low G/C content and a high percentage of DNA with 5-mers of exclusively A/T nucleotides ( Fig. 5C and D), both of which disfavor nucleosome formation (62,63). This would suggest that Mit1 may play a critical role in moving nucleosomes onto DNA sequences that are energetically unfavorable for nucleosome positioning.…”
Section: ⌬Phd and Mit1mentioning
confidence: 99%